Conservation and selection of plus trees of Pongamia pinnata in Bali, Indonesia - NI LUH ARPIWI; I GUSTI AYU SUGI WAHYUNI; I KETUT MUKSIN; SUTOMO SUTOMO (Biodiversitas Journal of Biological Diversity, 2018)
Arpiwi  NL, Wahyuni IGAS, Muksin IK, Sutomo. 2018. Conservation and selection of plus trees of Pongamia pinnata in Bali, Indonesia. Biodiversitas 19: 1607-1614. Pongamia pinnata (L.) Pierre or commonly known as pongamia is a tropical legume tree produces oil seeds for biodiesel feedstock. The aims of present study were mapping growth sites of pongamia in Bali,  counting the number of trees and selecting plus trees based on growth parameters such as total height, clear bole height, diameter at breast height, canopy width, and oil content. Method of plus tree selection was comparison tree where one candidate tree was compared with 5 nearby check trees from each village. A total of 126 pongamia trees were found in coastal beach of Bali. The majority of trees were in the north west of the island.  Temperature ranges from 26-28oC, humidity ranges from 74-80% and altitude 5-50 meters above sea level. Eight pongamia plus trees were selected from 4 villages namely Kalibukbuk, Pengulon, Pemogan, and Sanur. In conclusion, pongamia was mostly distributed in the northern-west part of the Bali Island of Buleleng District. Lower number of trees was also found in the southern and western part of the island. Trees either scattered or grown in small groups. The number of pongamia tree in Bali is small and this needs further action for conserving the species.